2022
DOI: 10.3389/fonc.2021.718684
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Submucosal Dissection for Early Gastric Cancer in Elderly vs. Non-Elderly Patients: A Systematic Review and Meta-Analysis

Abstract: ObjectiveThis study aimed to review the applicability and complications rate associated with endoscopic submucosal dissection (ESD) for early gastric cancer in elderly patients.MethodsDatabases of PubMed, Embase, CENTRAL, and ScienceDirect were searched till 15th April 2021. All types of studies comparing ESD in the elderly vs non-elderly were included. Subgroup analysis was conducted for the following groups: ≥80 years vs <80 years, ≥75 years vs < 75 years, and ≥65 years vs <65 years.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Therefore, our study suggests that ESD is considerably safe in patients aged ≥85 years. The perforation rate was significantly higher in the ≥85 years group, as pointed out in a previous meta-analysis [ 44 ]. However, the total AE rate in the ≥85 years group was not significantly different from those in the other groups in this study.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Therefore, our study suggests that ESD is considerably safe in patients aged ≥85 years. The perforation rate was significantly higher in the ≥85 years group, as pointed out in a previous meta-analysis [ 44 ]. However, the total AE rate in the ≥85 years group was not significantly different from those in the other groups in this study.…”
Section: Discussionsupporting
confidence: 65%
“…Although the rate of antithrombotic drug use was significantly higher in the ≥85 years group, no significant difference was observed in the rate of postoperative bleeding. None of the patients aged ≥85 years in this study had aspiration pneumonia, although a previous study reported an increased incidence of aspiration pneumonia in elderly patients [ 6 , 8 , 13 , 44 ].…”
Section: Discussionmentioning
confidence: 65%
“…Regarding age, a recent meta-analysis revealed that elderly patients tended to be at increased risk of perforation, including both intraoperative and postoperative types, with a significantly increased risk among ≥80-year-old patients. 16 In general, the thickness of the gastric wall decreases due to mucosal atrophy with aging. 17 Elderly patients with a thin gastric wall may thus be at greater risk of perforation.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis identified the following as risk factors for perforation: liver disease, location in the upper stomach, a resection size > 20 mm, submucosal invasion, operation time > 2 h, depressed or flat lesions, and piecemeal resection [ 59 ]. Another meta-analysis, this time comparing gastric ESD in elderly and non-elderly patients, found a trend for significantly increased perforation risk among patients aged >80 years [ 60 ].…”
Section: Endoscopic Resectionmentioning
confidence: 99%